1998
DOI: 10.1086/306186
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Transitions in Cygnus X‐1 and Other Black Hole X‐Ray Binaries

Abstract: We show that the model proposed by Esin, McClintock & Narayan (1997) for the low state, intermediate state and high state of the black hole soft X-ray transient, Nova Muscae 1991, is consistent with the spectral evolution of the black hole X-ray binary, Cyg X-1, during the hard-to-soft state transition observed in 1996. We also apply the model to the outbursts of two other black hole X-ray transients, GRO J0422+32 and GRO J1719−24.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
297
3
5

Year Published

2014
2014
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(337 citation statements)
references
References 94 publications
(153 reference statements)
32
297
3
5
Order By: Relevance
“…However, this was during the transition and VLA monitoring towards the end of the high/soft state period showed that, as found during previous state changes, the radio flux had dropped to ∼5 mJy (Zhang et al 1997b). Some authors (Belloni et al 1996, Esin et al 1998 have concluded that Cyg X-1 did not fully reach the soft/high state on this occasion in which case we may expect the radio source to not have disappeared as before. However, it should be noted that the radio source of GX339-4 diminishes during its X-ray intermediate/high state (Fender et al 1999 in prep) and, given the many similarities between these two systems in terms of their X-ray and radio properties, we may expect Cyg X-1 to behave likewise.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…However, this was during the transition and VLA monitoring towards the end of the high/soft state period showed that, as found during previous state changes, the radio flux had dropped to ∼5 mJy (Zhang et al 1997b). Some authors (Belloni et al 1996, Esin et al 1998 have concluded that Cyg X-1 did not fully reach the soft/high state on this occasion in which case we may expect the radio source to not have disappeared as before. However, it should be noted that the radio source of GX339-4 diminishes during its X-ray intermediate/high state (Fender et al 1999 in prep) and, given the many similarities between these two systems in terms of their X-ray and radio properties, we may expect Cyg X-1 to behave likewise.…”
Section: Resultssupporting
confidence: 49%
“…When Cyg X-1 enters the less common soft X-ray state the accretion disc extends much further towards the black hole and the ADAF is restricted to the corona (Esin et al 1998). Increased activity in the disc causes additional heating and ionization of the stellar wind, resulting in a loss of the Hα emission line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more realistic model was introduced by Esin et al (1997;see also Narayan et al 1996;Narayan et al 1997;Esin et al 1998Esin et al , 2001, where the generic corona was replaced by a more physical Advection Dominated Accretion flow (ADAF; Narayan & Yi 1994, 1995Abramowicz et al 1995). In our interpretation of the q-shaped curve, we will start from the Esin et al (1997) model and will expand it to take into account the wealth of new information that has become available since then.…”
Section: Introductionmentioning
confidence: 99%